Study of transitory phenomena at connecting the capacitive loads to an AC power source - Niculescu, Titu; Marcu, Marius; Popescu, Florin Gabriel (Journal of Advanced Computer Science & Technology, 2015)
This paper presents a new and a modern method for study the inductive-capacitive circuits which are connected to an AC power source, using modern methods based on digital technology and software used in engineering applications. The capacitive circuits which are switched on an AC power source at the initial moment are presented below. We can determine the capacitor current variation forms, the capacitor voltage in a transient regime by using virtual mediums, in two different regimes: the oscillating regime and the-periodic regime. Each presented case contains an analytical presentation of the phenomenon, but it also contains the diagrams of current and voltage capacitors. The diagrams were obtained by two methods, which use MATLAB package. These diagrams are compared with experimental measurements obtained with a data-acquisition system produced by National Instruments using LABVIEW software.